Mastering new technologies: does it relate to teleworkers’ (in)voluntariness and well-being? - Dias, Paulo (2022)
Purpose: This study aims to examine the associations among mastering new technologies, teleworkers’ voluntariness and involuntariness and employee well-being (i.e. work engagement and exhaustion). To the best of the authors’ knowledge, no studies have explored the relationships among these constructs in the same conceptual model. Design/methodology/approach: Data were collected from a sample of 451 individuals performing telework in Portugal. AMOS was used to test all hypotheses of the study. Findings: The findings showed a positive relationship between mastering new technologies and teleworkers’ voluntariness and a negative relationship between mastering new technologies and teleworkers’ involuntariness. However, contrary to expectations, voluntariness in teleworking was not significantly related to either work engagement or exhaustion. However, consistent with the theoretical background of self-determination theory, involuntariness in teleworking was negatively related to work engagement and positively related to exhaustion. Originality/value: This study contributes to the literature by addressing the analysis of telework-related variables that may impact workers’ well-being. Implications for human resource management policies and knowledge management are discussed.